The Influence of Cultural Context on the Mastery of Arabic Vocabulary - Muhamad Hasyim; Siti Halimatussa’diyah; Suci Rizki Lealadani; Zuhapandi; Siti Nurfy; Sukarta; Muhammad Hayyi; Muhammad Alfi Aziz Akbar (Journal of Islamic Religious Studies, 2026)
Arabic vocabulary mastery has become an essential aspect of Arabic language learning because vocabulary functions as the foundation for communication, comprehension, and language production. However, vocabulary learning is frequently conducted through memorization-oriented approaches that limit students’ contextual understanding and communicative competence. Therefore, this study aimed to examine the influence of cultural context on the mastery of Arabic vocabulary by analyzing how sociocultural experiences, contextual interaction, and culturally grounded instructional practices contribute to vocabulary comprehension, retention, contextual meaning-making, and communicative competence. This study employed a qualitative approach using a literature review design. The data sources consisted of scholarly books and journal articles published within the last ten years related to Arabic vocabulary learning, sociocultural theory, contextual learning, and Arabic language pedagogy. Data were collected through systematic documentation and literature exploration from relevant academic publications and analyzed using descriptive qualitative content analysis involving data reduction, thematic categorization, interpretation, and synthesis. The findings revealed that cultural context significantly improved students’ understanding and retention of Arabic vocabulary because learners interpreted lexical meaning through authentic communication, social interaction, cultural narratives, visual representation, and contextual learning experiences. The study also found that communicative, constructivist, multimodal, and technology-based instructional approaches strengthened learners’ communicative competence and contextual vocabulary acquisition. Furthermore, culturally contextualized vocabulary instruction was conceptually supported by constructivist, sociocultural, and contextual learning theories emphasizing meaningful interaction and cultural mediation in language learning. This study concludes that integrating cultural context into Arabic vocabulary instruction contributes significantly to meaningful vocabulary mastery, communicative language use, and culturally responsive Arabic language pedagogy.